Human Induced Pluripotent Stem Cell-Derived TDP-43 Mutant Neurons Exhibit Consistent Functional Phenotypes Across Multiple Gene Edited Lines Despite Transcriptomic and Splicing Discrepancies - Smith, Alec S. T.; Chun, Changho; Hesson, Jennifer; Mathieu, Julie; Valdmanis, Paul N.; Mack, David L.; Choi, Byung-Ok; Kim, Deok-Ho; Bothwell, Mark (Frontiers in Cell and Developmental Biology, 2021)
Gene editing technologies hold great potential to enhance our ability to model inheritable neurodegenerative diseases. Specifically, engineering multiple amyotrophic lateral sclerosis (ALS) mutations into isogenic cell populations facilitates determination of whether different causal mutations cause pathology via shared mechanisms, and provides the capacity to separate these mechanisms from genotype-specific effects. As gene-edited, cell-based models of human disease become more commonplace, there is an urgent need to verify that these models constitute consistent and accurate representations of native biology. Here, commercially-sourced, induced pluripotent stem cell-derived motor neurons, edited to express ALS-relevant mutations in TDP-43, were compared with in-house derived lines likewise engineered to express the same disease-causing mutations. Our results highlight electrophysiological and mitochondrial deficits in these edited cells that correlate with patient-derived cells, suggesting a consistent cellular phenotype arising from TDP-43 mutation. However, significant differences in the transcriptomic profiles and splicing behavior of the edited cells underscores the need for careful comparison of multiple lines when attempting to use these cells as a means to better understand the onset and progression of ALS in humans.